Answer:
Hello the answer to your question is 0.4 sec.
Step-by-step explanation:
Hope this helps
Answer:
51
Step-by-step explanation:
11+(-7)^2-9 - original
11+49-9 - square the -7, since its in brackets the negative applies too and a negative x a negative = positive, so it ends up as 7x7+49
60-9 - add both positives 11+49=60
51 - subtract 9 from 60, 60-9=51
To get the inverse of a function interchange
the x's with the y'x and solve for y, as follows:
y=5x-7
Interchange to get:
x=5y-7
Solve for y to get:
y=(1/5)x+(7/5)
so I think it might be c
Answer:
mean: 26
median: 28
mode: 28
range:19
Step-by-step explanation:
hipe this helped hun